(3efgGL GdJMbjb heMGSf GdJdajb aj CUhd GdOjfs - (3jMji Hf MSf Hf ehSi GdbQTjs ((3Ydi Hf eMeO Hf EOQjS Hf OGhO Hf SdjeGf s)
(3ChdgG (B:s
(3GdMeO ddg GdOGd Ydi PGJg hUaGJg HYLGFH eUfhYGJg , GdcGTa Yf YOdg hMceJg s
(3BNQgG (B:s
(3hGdCUd YOe GdLhGR ajHbi gPG GdLhGR ai Mb ZjQge efJajkG Ydi GdCUd s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3Ydi MhGTjgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds